Minimal residual disease surveillance at day 90 predicts long-term survival in pediatric patients with T-cell acute lymphoblastic leukemia. Issue 14 (5th December 2020) - Liu, Xiaoming; Zou, Yao; Chen, Xiaojuan; Wang, Shuchun; Guo, Ye; Yang, Wenyu; Zhang, Li; Chen, Yumei; Zhang, Yingchi; Zhu, Xiaofan
Abstract: To evaluate the optimal time to monitor minimal residual disease (MRD) for pediatric patients with T-cell acute lymphoblastic leukemia (T-ALL). Children newly diagnosed with T-ALL were treated per the CCLG-ALL2008 protocol in our hospital. MRD was monitored at days 15, 33 and 90, and the patients were stratified as low-, intermediate- or high-risk according to MRD at days 33 and 90. The 5-year event-free survival (EFS) and overall survival (OS) rates for all patients were 60.1 ± 5.6% and 63.1 ± 5.6%, respectively. The median follow-up time was 54 (0.3–120) months. Univariate analysis showed that the 5-year EFS rate correlated with MRD at days 33 and 90 ( p < .01). Multivariate analysis demonstrated that only MRD at day 90 and involvement of the central nervous system (CNS) were independent prognostic factors. MRD at day 90 likely provides better prognostic value for pediatric T-ALL patients. Clinical Trial Registration: ClinicalTrials.gov identifier: NCT00707083